Human Interface and the Management of Information. Information, Knowledge and Interaction Design : 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings /: Information, Knowledge and Interaction Design : 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available